Effects of exchange vs. controlled diet on biochemical, body composition and functional parameters in elite female soccer players - San Atanasio, S. A.; Maroto-Izquierdo, S.; Sedano, S. (PLOS ONE, 2023)
Due to the increasing level of professionalism, the high frequency of competitions, and the alarming injury rate observed in elite female soccer players, multidisciplinary strategies, including nutritional monitoring, need to be implemented. This study aimed to quantify energy, macronutrient and micronutrient intakes during the competitive period and to analyze the effects of two different nutritional interventions on nutritional knowledge, anthropometric data, biochemical values and physical performance. 19 elite female soccer players were randomly divided into two groups: the controlled-diet group (CG, n = 10), that followed a diet based on pre-established menus, and the exchange-diet group (EG, n = 9), that designed their own menus with an exchanged list. A cross-sectional study was designed to evaluate the dietary intake, while an experimental randomized controlled trial was designed to compare the effects of both 12-week nutritional interventions. Total energy, CHO, PROT, fibre and micronutrients intakes were below the general recommendations for athletes while, total and saturated fat intakes were above these. Moreover, there were no differences in diet during weekdays, pre-competition and competition days. The study also revealed a low nutritional knowledge and exchanged diet has demonstrated to be a better strategy to improve this. Biochemical monitoring showed that participants presented decreased concentration of haemoglobin and controlled diet may lead to greater effects on haemoglobin concentration and in anemia prevention. Both EG and CG showed significant reduction on skinfolds sum after intervention, but no significant differences were observed in thigh and calf indices. However, no significant changes were observed in soccer-related skills for any group.